Portfolio Efficiency Analysis of UNVR and SMGR Using the Efficient Frontier Approach: A Comparative Study in the Framework of Indonesia’s Green Economy Commitment - Poppy Yuliani; Hardiansyah Hardiansyah; Nicko Albart (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research examines the efficiency of investment portfolios comprising PT Unilever Indonesia Tbk (UNVR) and PT Semen Indonesia Tbk (SMGR) by applying the Efficient Frontier method, contextualized within Indonesia’s commitment to a green economy. The study’s novelty lies in its integration of quantitative financial modeling with the broader agenda of low-carbon national development. The primary aim is to assess and compare the risk-return characteristics of UNVR and SMGR stocks and to identify the most optimal portfolio composition. The analysis utilizes daily stock price data from 2024 and includes calculations of returns, risk (standard deviation), the Sharpe ratio, and stock correlation. Empirical findings indicate that UNVR yields an expected return of -0.24% with a 2.50% standard deviation, while SMGR shows an expected return of 0.26% with a 2.17% standard deviation. The correlation coefficient of 0.081 between the two stocks reflects a weak relationship, highlighting the potential for effective diversification. The combined portfolio demonstrates superior efficiency in balancing risk and return compared to holding individual stocks. These results suggest that investors can align sustainability goals with diversification strategies to advance Indonesia’s green economic objectives.